2011
DOI: 10.1016/j.psychres.2011.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Tactile body image disturbance in anorexia nervosa

Abstract: Body image disturbances are central to anorexia nervosa (AN). Previous studies have focused mainly on attitudinal and visual aspects. Studies on somatosensory aspects thus far have been scarce. We therefore investigated whether AN patients and controls differed in tactile perception, and how this tactile body image related to visual body image and body dissatisfaction. The Tactile Estimation Task (TET) measured tactile body image: Two tactile stimuli were applied to forearm and abdomen, and, while blindfolded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 54 publications
10
128
2
3
Order By: Relevance
“…Our results on pure tactile detection are not fully in line with those by Keizer et al (2011), who described unusual somatosensory performance in eating disorders participants. The authors found that as compared to controls, AN patients need a lower pressure to detect a simple stimulus on the abdomen, whereas they have a worse discrimination threshold when asked to discriminate between one or two touches on the abdomen or on the arm.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results on pure tactile detection are not fully in line with those by Keizer et al (2011), who described unusual somatosensory performance in eating disorders participants. The authors found that as compared to controls, AN patients need a lower pressure to detect a simple stimulus on the abdomen, whereas they have a worse discrimination threshold when asked to discriminate between one or two touches on the abdomen or on the arm.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with this view, we and other authors have suggested that primary tactile processing responsible for detecting an object in contact with the skin, can be anatomically and functionally dissociated from a secondary higher-order tactile processing, such as the discrimination of the sizes of objects touching different body parts (Serino et al, 2008;Gallace and Spence, 2009;Spitoni et al, 2010Spitoni et al, , 2013 We have proposed that, in order to extract metric information from the skin surface, the brain has to link information related to the single locations on the skin where touch is applied with a representation of the stimulated body part, and therefore, a "tactile size estimation task" can be used as an implicit proxy of the body representations. (Keizer et al, 2011(Keizer et al, , 2012) used a tactile size estimation task to study tactile performance in patients suffering from AN and they found that relative to controls, AN patients overestimated the distance between two tactile stimuli for the stimulated body parts. According to the authors, this evidence result from top-down influences of body dissatisfaction on the body representations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az egyik irányzat képviselői a test percepciójának multiszenzoros károsodásaként [56] vagy általános szomatoszenzoros zavar részeként [57,58] értelmezik a testkép-zavart, beleértve a taktilis, az interoceptív és a testi percepció, illetve ezek integrálásának érintettségét. Taktilis anhedoniaként [58] emlegetik azt a jelenséget, hogy a gyengéd érintést az anorexiás páciensek kevésbé érzé-kelik, illetve kevesebb kellemességérzést csatolnak hozzá.…”
Section: A Testképzavar Mint Az Anorexia Nervosa Magtüneteunclassified
“…Taktilis anhedoniaként [58] emlegetik azt a jelenséget, hogy a gyengéd érintést az anorexiás páciensek kevésbé érzé-kelik, illetve kevesebb kellemességérzést csatolnak hozzá. Az interoceptív deficit befolyásolhatja a test teljes reprezentációját, a testtudatosság alakulását [59].…”
Section: A Testképzavar Mint Az Anorexia Nervosa Magtüneteunclassified